The Effect of Humic Acid and Silicic Acid on P Adsorption by Amorphous Minerals - , Eko Hanudin ([Yogyakarta] : Elsevier, 2014)
Andisol is a soil with high P adsorption, this is due to high content in reactive amorphous materials. The present study was conducted to compare humic acid and silicate acid in blocking the P adsorption on amorphous minerals. The results indicated that the old and young formation of parent materials were not different in reactivity of the amorphous minerals and able to adsorb P &gt